Venice’s Ceremonial Treatment of the Ottoman and Safavid Envoys in Comparative Perspective - Guliyev, Ahmad (My University, 2020)
Taking a comparative perspective and drawing on the documents from the Venetian State Archives, the paper attempts to examine a ceremonial treatment of the Ottoman and Safavid diplomats in Venice. Both the Ottoman and Safavid envoys usually were graciously received in Venice. However, the degree of the Venetian hospitality was subject to changes and varied in accordance to the importance of the incoming mission and overall nature of its relations with the Ottomans and Safavids. It appears from the receptions of the Ottoman and Safavid diplomats in Venice that during the sixteenth and early seventeenth centuries, the ceremonial positions of the sultan’s envoys were equal or mostly above that of the Qızılbaş representatives. As it is evident from the Safavid Asad bey’s case in 1600, in its treatment of the Safavid envoys, Venetian government pursued a cautious policy and tried not to antagonize the Ottomans. Furthermore, the Ottoman factor had enduring impact both on the nature and on the dynamics of the Safavid-Venetian relations.
Osmanlı Ve Safevî Elçilerinin Venedik'te Kabul Törenleri Karşılaştırmalı Perspektifte
Keywords: Safavid-Venetian relations; Ottoman-Venetian relations; Safavid envoys